Molecular Neurodegeneration - Bu, Guojun; Xu, Huaxi
Molecular Neurodegeneration is an open access, peer-reviewed journal that encompasses all aspects of neurodegeneration research at the molecular and cellular levels. Neurodegenerative diseases collectively refer to neurological disorders that result from neurodegeneration and include, but are not limited to, Alzheimer's disease, Parkinson's disease, Huntington's disease, and prion diseases. These diseases, which are often associated with advanced aging and display varying degrees of dementia, have become a significant public health issue as humans live longer and the aging population grows larger. Recent advances in the molecular and cellular mechanisms underlying the pathogenesis of these neurodegenerative disorders have allowed for a better understanding of the disease mechanisms.